The relationship between constructions and units in Spanish phraseology (Islas, 2022)
ABSTRACTIntroduction: For phraseological studies, the relationship between fixedness and variation is an essential one, given the need of updating some concepts after the epistemological shift of the grammatical theories which, for the first time, include phrasemes in their object of study. This article deals with the dichotomy opposing a unit (element selected in a paradigm available) and a construction (combination of available units).Methods: The paper approaches the relationship between constructions and units in Spanish phraseology from the different views of: the Lexique-Grammaire school, Cognitive Grammar and the Grammar of Constructions. It starts with a review of the criteria of inclusion and exclusion, as well as the structural systemic analysis of a series of phraseological patterns for these trends, and then analyzes these theoretical considerations in a group of phraseological units.Results: Phrasemes have an internal syntax, as constructions, and an external syntax, as units. The former governs the fixity and idiomaticity of the expression itself, the latter governs their combinations with their immediate context, making them doubly idiomatic: internally and as components of another phrasing, in which they are imbricated. This characteristic can affect collocations, idioms, LVC, phrasal verbs, proverbs or constructive idioms. The case of adverbial idioms is prototypical in this sense, since, although they are (by definition) totally invariable in their internal syntax, nothing prevents them from forming a larger phraseme with a lesser degree of fixity, forming an imbricated collocation with a verb or a verbal idiom.Conclusions: We can say, without self-contradiction, that phrasemes are fixed and variable at the same time. The principle of imbrication links two syntactic levels corresponding to the different phraseological «spheres» (in Corpas´ sense): for the includer (collocation), fixity implies the norm, while, for the includer (idiom), it implies the system.
Keywords: construction Grammar; constructional idiom; collostructions; colocation; phrasal verb; imbrication principle